Effects of silicon on the wear behaviour of cobalt-based alloys at elevated temperature - Çelik, H; Kaplan, M (Elsevier Science Sa, 2004)
In this study, are presented and discussed effects of silicon on the abrasive wear behaviour at elevated temperatures of cobalt-based alloys such as Co-28Cr-4W-1.1C-3.2Si, Co-28Cr-4W-1.1C-4.1Si, Co-28Cr-4W-1.1C-5.2Si, respectively. Wear resistance of the materials were measured by a two body pin-on-disk wear tester with SiC and Al2O3 abrasives. The hardness of stellite 6 alloy increased with silicon addition. Wear resistance of stellite 6 with silicon addition has increased at low temperature but, decreased at high temperature. Microstructure of samples has been investigated by optical and SEM techniques. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Vickers hardness value; cobalt-based alloys; stellite 6 alloy